ANALISA KEPUASAN PENGGUNA TERHADAP KUALITAS APLIKASI TICKET MONITORING PT. INFRASTRUKTUR TELEKOMUNIKASI DENGAN METODE WEBQUAL - Ferly Andriansyah; Nining Suryani; Sukmawati Anggraeni Putri (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
The Helpdesk as Single Point Of Contact (SPOC) is a communication facility between customers or users and a support team of the company providing the product or service and the user usually complains or questions via telephone or email. Because currently the helpdesk staff often complain that the website being used is often error / slow, so the writer analyzes the website quality measurement, measuring the quality of the website can be done with tools or surveys. In this study, web quality is measured by users based on the measurement of website quality using webqual 4.0. The measurement of web quality on webqual 4.0 is done by the web user so that the measurements taken will help the web manager to adjust the quality of the web according to the user's perceptions. The research objective is to find out how effective the Ticket Monitoring System is for Users. To find out the effect of the system on what data information is obtained by the user. To find out the difficulties and convenience for each user in using the system.